2008
DOI: 10.4103/0378-6323.38402
|View full text |Cite
|
Sign up to set email alerts
|

Many faces of cutaneous leishmaniasis

Abstract: In Pakistan, an endemic country for CL, the possibility of CL should be kept in mind while diagnosing common dermatological diseases like erysipelas, chronic eczema, herpes zoster, paronychia; and uncommon disorders like lupus vulgaris, squamous cell carcinoma, sporotrichosis, mycetoma and other deep mycoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
3
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 0 publications
8
117
3
6
Order By: Relevance
“…This contrasts with numerous reports on atypical cases from the Mediterranean basin (12) and from other countries, including Pakistan (5-7,11,13,17), India (18), Iran (8,9) and Lebanon (19), where the major infective species is L. major. In these publications, the clinical polymorphism of the disease has been related to parasite dependent factors, such as virulence of the species (5,6,8,9,18), the vector (12), and geographical region where infection took place (11,12,18), and to the host, such as lesion localization (5,8) and immune response (5)(6)(7)(8)11,12,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with numerous reports on atypical cases from the Mediterranean basin (12) and from other countries, including Pakistan (5-7,11,13,17), India (18), Iran (8,9) and Lebanon (19), where the major infective species is L. major. In these publications, the clinical polymorphism of the disease has been related to parasite dependent factors, such as virulence of the species (5,6,8,9,18), the vector (12), and geographical region where infection took place (11,12,18), and to the host, such as lesion localization (5,8) and immune response (5)(6)(7)(8)11,12,18).…”
Section: Discussionmentioning
confidence: 99%
“…Its global prevalence varies between 0.17% and 2.5%, according to some case series from the Middle East (6,11). It is clinically discernible by one or more plaques composed of papules or pseudo-vesicles, located on the head (10,12), back (8,9), abdomen (13) or lower limbs (7), forming a lineal pattern and satellite lesions that involve one or more dermatomes that do not cross the median line (6,8,12).…”
mentioning
confidence: 99%
“…The diagnosis of CL was mainly based on the clinical criteria proposed by Kubba and AI-Gindan. [12] In typical cases treatment was initiated after clinical diagnosis while in atypical/ doubtful cases, imprint smears for Leishman Donovan (LD) bodies and tissue smears for histopathology were taken. As facilities for Novy-MacNeal-Nicolle (NNN) culture medium and PCR were not available in this institute so unproven cases were referred to higher centre for further workup.…”
Section: Methodsmentioning
confidence: 99%
“…[14] This observation suggests that outdoor activities increase the exposure to vector in this age group. Most studies show male preponderance for CL [2,12] but some studies describe that females are affected more than males, [9,15] while in few studies sex difference was not observed. [11,13] In our study, females outnumbered the males, the reason for female preponderance is that high risk activities (grass cutting, cattle rearing and field work) are handled by females as per culture of this region.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation